HASIL BELAJAR MODEL MaM DAN TS DENGAN MEMPERHATIKAN SIKAP TERHADAP MATA PELAJARAN - Ana Purnamasari; Yon Rizal; Tedi Rusman (FKIP Unila, 2015)
This research was aimed at finding the comparison on the average result study of IPS Terpadu by using Make a Match learning model (MaM) and Talking Stick (TS) by focusing on the attitude towards IPS Terpadu. The method used was comparative with experimental approach. The population were 101 students with a total sample of 51 students which was determined by cluster random sampling technique. The result showed that: 1) there is a difference between the average of result study between MaM and TS learning model, 2) there is a difference on the average of result study between students who had positive and negative attitude towards IPS Terpadu, 3) there is an interaction between learning model and attitude towards IPS Terpadu, 4) there is a difference on the average of result study by using MaM and TS among positive students, and 5) there is a difference the average of result study by using MaM and TS among sttudents who are negative.Penelitian ini bertujuan mengetahui perbandingan rata-rata hasil belajar IPS Terpadu menggunakan model make a match (MaM) dan talking stick (TS) dengan memperhatikan sikap terhadap mata pelajaran IPS Terpadu. Metode yang digunakan adalah komparatif dengan pendekatan eksperimen. Populasi 101 siswa dengan jumlah sampel sebanyak 51 siswa yang ditentukan dengan teknik Cluster Random Sampling. Hasil penelitian menunjukkan; 1) ada perbedaan rata-rata hasil belajar antara model MaM dan TS; 2) ada perbedaan rata-rata hasil belajar antara siswa yang memiliki sikap positif dan negatif terhadap mata pelajaran IPS Terpadu; 3) ada interaksi antara model pembelajaran dengan sikap terhadap mata pelajaran IPS Terpadu; 4) ada perbedaan rata-rata hasil belajar menggunakan model MaM dan TS bagi siswa bersikap positif; dan 5) ada perbedaan rata-rata hasil belajar menggunakan model MaM dan TS bagi siswa bersikap negatif.Kata kunci: MaM, sikap, TS